PENGUATAN BUDAYA LITERASI PADA ANAK USIA DINI MELALUI “GERNAS BAKU” - Zaidatul Arifah (Institut Islam Nahdlatul Ulama Temanggung, 2018)
Writing this journal aims to find out how to strengthen the culture of literacy in early childhood and how the implementation of strengthening literacy culture in early childhood through